Analysis of immune responses to recombinant proteins from strains of Mycoplasma mycoides subsp. mycoides, the causative agent of contagious Bovine pleuropneumonia - Pérez Casal, J.; Prysliak, T.; Maina, T.; Wang, Y.; Townsend, H.; Berverov, E.; Nkando, I.; Wesonga, H.O.; Liljander, Anne M.; Jores, Joerg; Naessens, Jan; Gerdts, V.; et al. (Elsevier, 2015)
Current contagious bovine pleuropneumonia (CBPP) vaccines are based on live-attenuated strains of Mycoplasma mycoides subsp. mycoides (Mmm). These vaccines have shortcomings in terms of efficacy, duration of immunity and in some cases show severe side effects at the inoculation site; hence the need to develop new vaccines to combat the disease. Reverse vaccinology approaches were used and identified 66 candidate Mycoplasma proteins using available Mmm genome data. These proteins were ranked by their ability to be recognized by serum from CBPP-positive cattle and thereafter used to inoculate naïve cattle. We report here the inoculation of cattle with recombinant proteins and the subsequent humoral and T-cell-mediated immune responses to these proteins and conclude that a subset of these proteins are candidate molecules for recombinant protein-based subunit vaccines for CBPP control.